PCA/PROFET: um projeto de formação de aprendizes para o trabalho (Araxá, 2007-2009) - Santos, Edenir Vitoria de Araujo (2010)
This work central focus is to analyze Araxá public politic, the kid and teenager program, which develop lots of subprograms to offer services to this public, like this analysis object, the formation and routing to work project. The empiric foundation of this research was about this institution and was realized by looking up documents from the period of time from 2007 to 2009 and by interviews. At the first moment, began with the perception of the project running and stages, the selection test, the capacitation courses, and the youth routing to the job market. In the document research it was used some descriptive reports made by the caseworker to observe the social condition of the teenagers included in the program. At the second moment, using semi-structured guides, interviews were realized with lots of people involved in the project, of different functions and participation forms: the local police agents, managers who work directly at the project, the human resources and courses coordinator, companies agents, mothers or guarantors of the teenagers who are actual participants or egressions, in the condition of dropout or success. The interviews objective was people perception about some specific questions, basing on the kind of the interviewee participation. With this research it was conclude that the project represent to the youth a big opportunity and because of this, they value the experience they live at work. The youth interviewee, like the participants major part, comes from poor family, with low income. Usually, these youths have to conciliate work and studies. The company agents, the managers and the police agents consider that the diligent and motivated teenagers, have also the opportunity of the first work. The research showed that the program represent a significant element at the social inclusion politic